Influence of Non-Thermal Plasma (DBD) On Infertility Male Semen with Low Sperm Motility and Dna Damage - Mazhir, Sabah N.; Hanon, Marwa S.; al-Ahmed, Hazim I.; Haddad, Reem A. (Iraqi Journal of Science, 2022)
Non-thermal plasma(Dielectric barrier discharge) has many uses including living tissue sterilization, inactivation of the bacteria, excimer formation, angiogenesis, and surface treatment. This research aim is to use cold plasma as a tool to search the effect of the dielectric barrier discharge system at room temperature on human sperm motility and DNA integrity. This work was performed on 60 human semen samples suffering from low motility; each sample was prepared by centrifugation method, then each semen sample was divided into two sections, the first section is before significant exposure to the plasma system (DBD) and the second section is after treatment with the DBD system at ambient temperature. Before and after exposure to non-thermal Plasma (DBD), DNA integrity and sperm motility were assessed, patients suffered from asthenospermia has a high level of DNA fragmentation than fertile male, ( 24.16±4.14) p<0.001 for untreated and after treatment the semen slide with dielectric barrier discharge the percentage decreases to (9.16±1.76) p>0.006, and the comet slide was (35.44±4.15) then the percentage decline to (19.86 ±2.44) these results have shown that cold plasma improves sperm motility and decreases from DNA damage in patients with medium and high level of DNA damage.